Diagnostic Accuracy of Computed Tomography with Intraoperative Findings in Prediction of Metastatic Cervical Lymph Nodes in Oral Squamous Cell Carcinoma by Taking Histopathology as Gold Standard: CT Accuracy for Cervical Node Metastasis in OSCC - Sagar, Bhavesh; Hamid, Kamran; Khalique, Abdul; Asghar, Sehrish; Irfan, Bilal; Mehak, .; Varsha, .; Devi, Priyanka (Pakistan Journal of Health Sciences, 2025)
Oral squamous cell carcinoma is a common cancer with a high risk of cervical lymph node metastasis. Accurate identification of metastatic nodes is vital for staging and treatment planning. Computed tomography (CT) is widely used for pre-surgical assessment, while intraoperative lymph node evaluation offers additional diagnostic value. Objectives: To assess the diagnostic accuracy of CT and intraoperative findings in predicting metastatic cervical lymph nodes in oral squamous cell carcinoma, using histopathology as the gold standard. Methods: A cross-sectional study was conducted at the Department OF Radiology, Dr. Ziauddin University Hospital, Karachi, from November 2023 to November 2024. A total of 323 patients with clinically suspicious oral squamous cell carcinoma underwent CT neck scans and intraoperative lymph node assessment based on size, consistency, shape, and adherence. Histopathology of resected nodes was the reference standard. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy were calculated. Results: The mean patient age was 51.5 years, with an average lymph node size of 20.9 mm. CT showed sensitivity 97.2%, specificity 84.6%, PPV 76.3%, NPV 98.4%, and accuracy 88.8%. Intraoperative scoring demonstrated sensitivity 89.3%, specificity 88.8%, PPV 80.3%, NPV 94.5%, and accuracy 89.2%. Conclusions: Both CT and intraoperative scoring demonstrated high diagnostic accuracy for detecting metastatic cervical lymph nodes. Their combined application is recommended to enhance staging, guide surgery, and improve patient outcomes.